2021
DOI: 10.1186/s40798-021-00390-y
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses to Low-Volume Interval Training in Women

Abstract: Interval training is a form of exercise that involves intermittent bouts of relatively intense effort interspersed with periods of rest or lower-intensity exercise for recovery. Low-volume high-intensity interval training (HIIT) and sprint interval training (SIT) induce physiological and health-related adaptations comparable to traditional moderate-intensity continuous training (MICT) in healthy adults and those with chronic disease despite a lower time commitment. However, most studies within the field have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 166 publications
1
17
0
2
Order By: Relevance
“…In a recent meta-analysis summarizing studies performed in healthy and unhealthy adults, Sultana et al (35) demonstrated that the completion of low-volume interval training induces greater improvements in maximum oxygen consumption (V Ȯ2 max) than MICT. More recent studies show that extremely low-volume interval training applied in laboratory or outdoor setting (,20 minutes per session) is sufficient for improving redox status, and insulin sensitivity and reducing blood pressure, and body fat in young adults (4,18,32). Furthermore, SIT protocols requiring few repetitions of very short sprints (#10 seconds) significantly enhance V Ȯ2 max and anaerobic power (6), likely because of the high-power generation characteristic of these bouts.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent meta-analysis summarizing studies performed in healthy and unhealthy adults, Sultana et al (35) demonstrated that the completion of low-volume interval training induces greater improvements in maximum oxygen consumption (V Ȯ2 max) than MICT. More recent studies show that extremely low-volume interval training applied in laboratory or outdoor setting (,20 minutes per session) is sufficient for improving redox status, and insulin sensitivity and reducing blood pressure, and body fat in young adults (4,18,32). Furthermore, SIT protocols requiring few repetitions of very short sprints (#10 seconds) significantly enhance V Ȯ2 max and anaerobic power (6), likely because of the high-power generation characteristic of these bouts.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that activating and building muscle, while participating in high intensity cardiovascular training improves metabolic system components (MacDougall et al, 1998;MacInnis & Gibala, 2017). These improvements allow total energy expenditure increases, beneficing the reduction of body fat content (Atakan et al, 2021;Skelly et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In response to training, many markers of skeletal muscle remodelling linked to insulin sensitivity are reportedly similar between males and females, including glycogen synthase and hexokinase protein expression 85 and mitochondrial content 93 ; although, one study has observed greater increases in GLUT4 protein content with training in males compared to females. 93 However, as has been noted previously, 20 studies simultaneously measuring sex differences in insulin sensitivity and associated muscle mechanisms with interval training are scarce. Taken together, while the available literature demonstrates greater improvements in insulin sensitivity following intense interval exercise in males compared to females (particularly with low-volume SIT), additional research is needed to elucidate potential mechanisms.…”
Section: Does Sex Influence Skeletal Muscle Mechanisms Contributing T...mentioning
confidence: 99%
“…Importantly, future studies should involve larger sample sizes and control for factors that may confound sex-based comparisons including proper matching between males and females, menstrual cycle phase, and oral contraceptive use. Given the greater proportion of male-only cohorts in muscle physiology research 115 including amongst studies within the HIIT/SIT literature, 20 , 116 more research involving exclusively females is also warranted to enhance our basic understanding of how exercise influences muscle insulin sensitivity in females.…”
Section: Does Sex Influence Skeletal Muscle Mechanisms Contributing T...mentioning
confidence: 99%
See 1 more Smart Citation